2014
DOI: 10.1088/0967-3334/35/9/1837
|View full text |Cite
|
Sign up to set email alerts
|

Pulse wave analysis with two tonometric devices: a comparison study

Abstract: Pulse wave analysis is a pivotal tool to estimate central haemodynamic parameters. Available commercial devices use applanation tonometry and have been validated against invasive catheterism. We previously observed differences on a radial second systolic peak (rSPB2) between two commonly used devices: SphygmoCor (AtCor, Australia) and PulsePen (DiaTecne, Italy). The aim of our study was to further quantify differences in radial and carotid signals from the two devices.We measured radial and carotid waveforms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…This finding supports the work of others [27,28,29]. Agnoletti et al [28] examined 618 T2DM patients and showed that across increasing tertiles of T2DM duration PWV increased significantly, while glycaemic control and renal function worsened [28].…”
Section: Discussionsupporting
confidence: 85%
“…This finding supports the work of others [27,28,29]. Agnoletti et al [28] examined 618 T2DM patients and showed that across increasing tertiles of T2DM duration PWV increased significantly, while glycaemic control and renal function worsened [28].…”
Section: Discussionsupporting
confidence: 85%
“…Similar comparisons of AIx estimations by different devices have been previously reported, evaluating various methodologies based on: (a) different pulse acquisition technique (ie, tonometry, oscillometry, photoplethysmography), (b) different signal processing techniques (ie, with or without transfer function, algorithms for inflection points identification), and (c) different arterial sites for wave reflection estimation (ie, finger, aorta, radial, brachial, carotid arteries) (Table ). It should be acknowledged that all these differences render the interpretation and explanation of the observed discrepancies in AIx measurements among various devices quite difficult.…”
Section: Discussionsupporting
confidence: 64%
“…However, the limits of agreement in carotid AIx measurement by SphygmoCor and PulsePen (around −15% to 26%) were somewhat narrower than the limits of agreement reported in our study. In another comparison study, Agnoletti et al found that PulsePen and SphygmoCor devices are not equivalent and provide different wave shapes (despite similar harmonics content) with a greater discrepancy observed on radial than on carotid derived parameters. Jatoi et al also assessed AIx measurements by three commercial devices (Arteriograph, Complior, and SphygmoCor) in 254 untreated hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse wave analysis, which can be observed on the commonly used device—SphygomoCor device (AtCor, Australia),30 is measured to estimate central haemodynamic parameters 31. SphygmoCor is used to perform the applanation tonometry on a radial artery with the methodology previously described 30.…”
Section: Methodsmentioning
confidence: 99%
“…SphygmoCor is used to perform the applanation tonometry on a radial artery with the methodology previously described 30. After a 10 min rest in the supine position, the brachial BP is obtained with the SphygomoCor device.…”
Section: Methodsmentioning
confidence: 99%